Beginning J2ME : From novice to professional - Li, Sing; Knudsen, Jonathan (New York Springer-Verlag, 2005)
This book describes how to program mobile telephones, papers, PDAs. and other small devices using Java technology.
Includes index.
Keywords: Công nghệ thông tin